Building an infrastructure project performance in the North-West Province Department of Public Works and Roads - Murwira, Davison; Bekker, Michiel (University of the Free State, 2017)
Building and infrastructure projects at the North-West Province Department of Public Works and Roads (NW DPWR) often perform poorly in terms of overrunning both the original approved timeline and the budget. Adding to poor time and cost performances, these projects often do not meet the desired functional requirements. This article reports on findings of a study which investigated the causes of these poor performances in the NW DPWR. Fifty potential causes of poor performance were identified from literature. These factors were grouped under three main related categories of owner-related, contractorrelated and consultant-related and were subjected to a questionnaire survey to identify the most critical causes of failure. The results were analysed using the Relative Importance Index (RII) and Spearman’s Rank Correlation Coefficients. The results indicated that the most significant causes of poor building and infrastructure project performance in the NW DPWR include underestimation of project cost, the lack of experience in executing projects, contractor’s cash-flow constraints, corruption and bribery during the bidding and contract award phase, as well as poor site management and supervision. Recommendations are made to prevent similar causes of projects failure in the NW DPWR in future.

Bou- en infrastruktuurprojekte by die Noordwes Provinsie se Departement van Openbare Werke en Paaie (NW DPWR) ondervind gereeld tydvertragings in projekvoltooiing sowel as probleme soos oorspandering en die gebrek aan voldoening aan funksionele spesifikasies. Hierdie artikel rapporteer resultate van ’n studie wat onderneem is ten einde die redes waarom projekte in die NW DPWR swak presteer, te ondersoek. Vanuit literatuur is vyftig potensiële redes vir projekfaling geïdentifiseer. Die redes is in drie verwante kategorieë gegroepeer, naamlik eienaarverwante, kontrakteurverwante en konsultantverwante kategorieë. Deur middel van ’n vraelysopname is die mees kritieke redes vir projekfaling geïdentifiseer. Die resulate is ontleed deur gebruik te maak van ’n Relatiewe Sterkte Indeks asook die Spearman Rangorde Korrelasie Koëffisiënte. Die resultate toon dat die mees beduidende redes vir projekfaling in NW DPWR sluit onderberaming van projekkoste, gebrekkige ervaring in projekimplementering, beperkte kontantvloei deur kontrakteurs, korrupsie en omkopery tydens die tenderproses en kontrakaanstellings, sowel as swak terreinbestuur en toesig in. Aanbevelings is gemaak om soortgelyke probleme met toekomstige projekte in die NW DPWR te beperk.
Keywords: Building; Construction projects; Cost overruns; Infrastructure; Project performance; Schedule delays; Relative importance index